Electric and acoustic stimulation during movement preparation can facilitate movement execution in healthy participants and stroke survivors - Marinovic, Welber; Brauer, S.; Hayward, H.; Carroll, T.; Riek, S. (Elsevier, 2016)
There has been increasing interest in the use of loud acoustic stimulation (LAS) to gain insight into the preparation and initiation of motor actions. Typically, LAS presented during movement preparation in healthy participants culminates in the earlier than normal initiation of the prepared movement and an increase in the magnitude of the response. Recent reports have shown LAS can also facilitate movement in chronic stroke survivors. This suggests that current therapies for motor recovery after stroke might benefit from employing such alternate methods of triggering movement. In this study we sought to test a new way to facilitate motor actions that could be of relevance in clinical settings. Five individuals with chronic motor impairments due to stroke and eight healthy young adults performed a functional reaching task in response to a visual go-signal. On 30% of the trials, LAS or electric stimuli (collectively, sensory stimuli) were unexpectedly presented in synchrony with the go-signal. Both healthy and stroke participants reacted with shorter latencies and executed faster responses when sensory stimulation was synchronized with the go-signal. We have replicated previous findings showing acoustic stimuli can aid movement execution in chronic stroke survivors and demonstrated the same type of effect can be achieved using electric stimulation. Thus, these two types of sensory stimuli can be easily integrated with current devices available to assist people with stroke to engage in rehabilitation efforts.